Pakistani Population under Dark Shadows Of Diabetes: Do we need a Different Protocol for Diagnosing Type-2 Diabetes Mellitus? - Khan, Sikandar Hayat; Khan, Muhammad Qaiser Alam; Hayat, Asma; Munir, Usman; Anwar, Muhammad; Ali, Asif; Ghani, Eijaz (Pakistan Armed Forces Medical Journal, 2025)
Type-2 diabetes mellitus(T2DM) is taking on a mammoth toll in subcontinental population. Current international guidelines to screen T2DM requires although inclusive of majority of T2DM cases, still remain exclusive of many cases especially in Asian population. WHO data suggests Pakistan to be third in terms of diabetes cases and predicted to lead the world by next decade and half. Our country needs holistic, dedicated and evidence-based country-specific approach to manage this incoming sweetening menace of our times. Recent researches including Diabetes Prevalence Survey of Pakistan(DPS-PAK) and Pakistan Recommendation for optimal management of Diabetes from Primary to Tertiary Care Level(PROMPT) studies identifies an immediate need for timely focus for the Pakistani population. A wholesome multi-prong strategy for T2DM is needed. Our study group planned to review diabetes screening for our locale. While the obesity patterns and BMI have already been acknowledged as “different”, we believe diagnostic screening age for T2DM to be varied for sub-continental population. We reviewed local and regional to trace down our normality definition for screening hyperglycemia. Any sensitive “medically defined stipulation for normality limit” for screening age mandates a well-researched evidence base with benefits likely to mitigate disease.  Our reviewed data consistently highlighted an emerging trend among youth and adolescence for developing hyperglycemia among the Asians communities at an early age especially so in Pakistani population. Therefore, we suggested a very robust and early age (1-8 years with high incorporating high anthropometric indices) for screening T2DM for Pakistani population followed by periodic monitoring.